Peran minat atletik dalam mempromosikan keterlibatan aktivitas fisik berbasis rumah siswa di tengah pandemi - Dela Cueva Panganiban, Teejay (Universitas Nusantara PGRI Kediri, 2022)
Sports and activity programs play a significant role in children's overall physical activity levels to allow them to benefit from participating in physical activity during the pandemic. The researcher seeks to provide guidelines that will benefit all students who participate in physical education. This study aimed to determine the interest in athletics and engagement in home-based physical fitness activities of pre-service physical education teachers at Batangas State University JPLPC-Malvar, to determine its implications for teaching physical education. It specifically addressed the respondents' level of interest in athletics, their engagement in home-based physical fitness activities, the significant relationship between the two variables, and suggested activities to increase respondents' interest in athletics through participation in home-based physical fitness activities. This descriptive-correlational study was conducted to assess 62 students enrolled in the Bachelor of Physical Education program at the Batangas State University JPLPC-Malvar campus. Using a self-made questionnaire and appropriate statistical measures, the obtained results revealed that the majority of respondents engage in home-based physical fitness activities; however, bodyweight training is more engaging than anaerobic exercise. The data also showed a significant relationship between athletic interest levels and home-based physical fitness activities. The majority of responders are pre-service physical education instructors. The recommended activities to increase respondents' interest in athletics can be accomplished through participation in home-based physical fitness activities.